Passive Control of Attachment in Legged Space Robots - Alessandro Gasparetto; Renato Vidoni; Tobias Seidl (Applied Bionics and Biomechanics)
In the space environment the absence of gravity calls for constant safe attachment of any loose object, but the low-pressure conditions prohibit the use of glue-type adhesives. The attachment system of freely hunting spiders, e.g. Evarcha arcuata, employs van der Waals forces and mechanical interlocking. Furthermore, detachment is achieved passively and requires little force. Hence, the spider serves as a model for a versatile legged robot for space applications, e.g. on the outer surface of a space station. In this paper, we analyse the dry attachment systems of E. arcuata and geckos as well as the kinematics of freely hunting spiders. We generalise the results of biological studies on spider locomotion and mobility, including the major movement and the position constraints set by the dry adhesion system. From these results, we define a simplified spider model and study the overall kinematics of the legs both in flight and in contact with the surface. The kinematic model, the data on spider gait characteristics and the adhesion constraints are implemented in a kinematic simulator. The simulator results confirm the principal functionality of our concept.